CORPORATE OWNERSHIP VARIABILITY AND AUDIT REPORT FILING OF LISTED NON-FINANCE FIRMS IN NIGERIA (Journal of Global Accounting, 2026)
This study evaluated the effect of corporate ownership variability on audit report filing in Nigeria. Specifically, it investigated the effects of managerial ownership, and family ownership on audit report filing attitude of early and late filers of audited financial report among listed non-finance firms on Nigerian Exchange Group. Adopting the ex post facto research design, the secondary data source such as the audited annual reports of 68 non-finance firms out of 101 non-finance firms listed on the floor of the Nigerian Exchange group sampled using the sample filtering non-probability sampling technique over a ten-year period ranging from 2015-2024, were extracted. Utilising the STATA ver 17 statistical software, relevance correlation and regressional analysis was conducted. Empirical findings showed that managerial ownership had weak, negative and no significant effect on audit report filing of early and late filers of annual financial report among listed non-finance firms in Nigeria (p-values 0.799 and 0.919; coefficients -0.005 and -0.0025). Also, family ownership (FAMO) had a negative and no significant effect on audit report filing of early and late filers of annual financial report among listed non-finance firms in Nigeria (p-values 0.864 and 0.199; coefficients -0.009 and -1.936). In essence, this study concluded that ownership structures do not operate with uniform potency across all reporting timelines; rather, their effects were mediated by the firm’s filing behaviour, internal governance quality, and regulatory responsiveness. The study therefore recommends that stakeholders in the non-finance sector of Nigeria should not rely solely on equity participation by Directors as a mechanism for improving audit report timeliness. Instead, regulatory bodies and corporate boards should prioritize strengthening external monitoring systems, audit process automation, and enforcement of reporting deadlines.
Keywords: Audit Report Filling; Corporate Ownership variability; Early Filers, Family ownership; Late Filers; Managerial ownership